Analisis Hukum Peran Serikat Pekerja (Studi Pada PT CS2 Pola Sehat Maros) - Sadikin Sahir; Irsyad Dahri; Mustaring Mustaring (Universitas Negeri Makassar, 2022)
Workers or laborers are the cogs that make the company always operate and produce. In the process of running a business, workers often become victims of arbitrariness carried out by employers by not giving workers rights. In an effort to ensure that there is no arbitrariness as described previously, the government makes labor laws that employers must comply with. On this basis, workers create a forum or organization that focuses on ensuring that their rights are fulfilled by the company and establishing good relations between workers and the company. This forum is called a trade union/labor union. Trade unions/labor unions are representatives of workers/labor in the company as representatives of workers expressing their aspirations in resolving disputes or building harmonious relationships with employers. The study was conducted by the researcher using a statue approach in normative legal research and a qualitative approach in empirical legal research. The purpose of this study is to analyze the extent to which the role of trade unions in its efforts to provide protection to workers and achieve good industrial relations legally. The population of the study were 101 members of PUK PT. CS2 Pola Sehat in Maros and the sample was 20 people. The data of the study were obtained from the results of filling out questionnaires, interviews, and observations made by the researcher. This study employed a simple statistical descriptive analysis to analyze the results of the survey questionnaire. Based on the results of the study, it is concluded that the trade unions at PT. CS2 Pola Sehat in Maros are active in carrying out their roles in resolving labor disputes, creating harmonious, dynamic, and fair as well as channeling the aspirations of workers.